The social costs of solar radiation management - Jacob Bronsther; Yangyang Xu (npj Climate Action)
Abstract In this essay, we argue that the all-things-considered “price” of Solar Radiation Management (SRM) is much higher than its modest technical costs would indicate. First, we estimate that Stratospheric Aerosol Injection (SAI) will generate between $0 and $809 billion annually in side-effect harms, while the number is likely to be considerably higher for Marine Cloud Brightening (MCB). Second, SRM would depend on unprecedented international cooperation and, therefore, risk global instability. Third, politicians may hesitate to support SRM since they may be held politically accountable for everyday “bad” weather as well as extreme weather events. Fourth, SRM poses “termination risks.” Finally, we observe that when the holistic, “true” cost of SRM is fully accounted for, the comparison between SRM and what we term “large-scale” Carbon Dioxide Removal becomes complex.